Hydrotherapy on Reducing Blood Sugar Levels in Patients with Type II Diabetes Mellitus in Ciputat Village, South of Tangerang City - Riris Andriati; Rita Dwi Pratiwi; Luthfi Muthoinah; Muh Firman Yudiatma; Sandeep Poddar (Window of Health : Jurnal Kesehatan, 2025)
Diabetes mellitus increases blood glucose levels (hyperglycemia) due to damage from insulin secretion and action. Diabetes mellitus is a chronic metabolic disorder characterized by high blood sugar levels. Symptoms felt in patients with Diabetes Mellitus are polydipsia, polyuria, polyphagia, as well as weight loss and tingling. Hydrotherapy is one method of treatment and healing using water to get a therapeutic effect or healing. This study aimed to determine hydrotherapy's impact on reducing blood sugar levels in patients with type II diabetes mellitus in Ciputat Village, South of Tangerang City. The research method in this study is quantitative research and has a quasi-experimental design. Sampling using a non-probability sampling technique with a sample of 68 respondents. Data analysis using the Wilcoxon test with a degree of significance p < 0.05. The results showed that the statistical test results for the Wilcoxon Test get a p-value of 0.00 < 0.05. This conclusion shows hydrotherapy's effect on reducing blood sugar levels in patients with type II diabetes mellitus in Ciputat Village, South of Tangerang City.